A Minimalist Analysis of Ergative Verbs in Yoruba - Olanrewaju, Emmanuel Omoniyi (Lingual Journal of Language and Culture, 2025)
Extant works on Yorùbá have identified some other different sub-classes of verbs in the language, based their classifications on functional, structural, semantic approaches and so on. However, little or no attention is yet to be paid to the sub-class of ergative verbs in the language. Therefore, this paper discusses the in-depth analysis of ergative verbs in Yorùba, detailing the strategies in the formation of ergative constructions in the language. Twelve (12) native speakers aged 65 and above were purposively selected for structured oral interview based on their proficiency. Data were subjected to syntactic analysis within the confine of the Minimalist Program. Ergative verbs in Yorùbá fall within both simple and complex verbs. In an ergative construction, the subcategorised DP object is copied to the specifier position of the tense phrase (TP) through the specifier position of the light verb phrase (vP) where the nominative case on the T-head (T0) is checked.  Yorùbá operates a null subject DP in an ergative construction, consequent upon this, it is invisible to a potential probe c-commanding it. Ergative features were identified on some transitive and splitting verbs. An object DP in an ergative construction occupies the specifier position of a verb phrase (VP) not for (accussative) case checking purpose. An object DP is only copied through the specifier position of the verb phrase (VP) to the specifier position of the outer light verb phrase (vP), an escape hatch that allows it visible to subsequent operations. The process of case checking is delayed at the VP domain so that the T-head (T0) will have it [+case] feature checked by raising the same object DP to the specifier position of the tense phrase (TP).